Analyzing the Potential Implementation of Environmental Accounting in the Preparation of Sustainable Natural Capital Accounts in Umbele Village - Wahyudin, Aan; Mustamin; Kahar, Abdul; Tenripada (Lafadz Jaya Publisher, 2025)
Nature inherently provides essential resources for human sustenance. Consequently, natural resources and environmental services are increasingly utilized. However, escalating population growth and rising income levels have led to a decline in the value and quality of these resources. Uncontrolled exploitation, environmental neglect, and inadequate structured recording pose significant threats to the sustainability of natural capital at the local community level. This study investigates the potential for implementing environmental accounting practices in Umbele Village to facilitate the preparation of sustainable natural capital accounts, utilizing primary data gathered through interviews and field observations. The findings reveal that the majority of Umbele's inhabitants heavily rely on natural resources, which are increasingly affected by environmental degradation and climate change. Current governmental interventions to address these challenges are perceived as insufficient, compounded by a lack of corporate responsibility.